(untitled) (Al Mitsali : Jurnal Penelitian dan Pendidikan Bahasa Arab, 2023)
The purpose of this study was to find out the process of muhadatsah learning in class VIII B students of SMPIT Ar-Raihan, and the problems faced by teachers and students in muhadatsah learning. The questions in this study include "How is the muhadatsah learning process for class VIII B students of Smpit Ar-Raihan Bandar Lampung?". This research is a qualitative descriptive study. The subjects in this study were class VIII B, which consisted of 21 students. Based on the research that has been done, the results of this study show that: 1) the process of learning muhadatsah in class VIII B students is planning before the learning process of muhadatsah in class is quite good, by fulfilling the requirements for implementing learning. The methods used by the teacher when teaching are quite varied, namely the lecture method, question and answer, practice, and games and the teacher also provides evaluations at home such as memorizing the material that has been delivered. 2) Problems of learning muhadatsah faced by teachers and students are educational background, not interested in learning muhadatsah, lack of motivation to learn, not attaching importance to learning, lack of mastery of muhadatsah vocabulary, difficulty in pronouncing muhadatsah, difficulty in memorizing muhadatsah texts, Difficulties in translating muhadatsah texts. So it can be concluded that the problems originating from teachers and students have an impact on the students’ point of view about difficult/difficult muhadatsah